Cross-scale operational oceanography in the Adriatic Sea. Issue 2 (3rd July 2019) - Ferrarin, Christian; Davolio, Silvio; Bellafiore, Debora; Ghezzo, Michol; Maicu, Francesco; Mc Kiver, William; Drofa, Oxana; Umgiesser, Georg; Bajo, Marco; De Pascalis, Francesca; Malguzzi, Piero; Zaggia, Luca; et al.
ABSTRACT: The oceanographic forecast capability in coastal seas is often limited by the capacity of the numerical models in correctly reproducing the complex morphology of the coastline and the exchange processes between the shelf and the open seas. In the marginal Adriatic Sea this task is of uppermost importance due to the presence of several coastal water bodies and rivers. We present here a new operational oceanographic system, called Tiresias, based on the unstructured grid model SHYFEM and representing the whole Adriatic Sea together with the lagoons of Marano-Grado, Venice and Po Delta. The novelty of this oceanographic system resides in the very high-resolution, up to 10 m, of the numerical mesh, and in the high spatial and temporal resolution of the forcing and boundary conditions that drive the forecasts. The forecast results are evaluated against sea temperature and salinity profiles, mean circulation fields derived from a regional ocean model, tide gauges and drifter trajectory. The presented results highlighted the capacity of Tiresias in forecasting the general circulation in the Adriatic Sea, as well as several relevant coastal dynamics, such as saltwater intrusion, storm surge and riverine waters dispersion.